ANALISA PENGARUH PENGGUNAAN CONTROLLER PADA FILTER AKTIF SHUNT TERHADAP PEREDAMAN DISTORSI HARMONISA - Suartika, I Made; Rinas, I Wayan (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p18, 2020)
The types of filters used to reduce harmonic distortion are passive filters, active filters and hybrid filters. The type of filter that usually uses the system controller is an active filter. In this study, an analysis of current harmonic distortion from the simulation results using matlabh according to the IEEE Std 519-1992 standard in existing conditions, active filter operating conditions, active filter operation using PID controllers and active filters based on Fuzzy Logic Controller. The simulation results of the three models used show that the resulting THDii still meets the IEEE Std 519-1992 standard, namely the THDi is still 8%, the simulation results for PID-based active filters are: pasa R = 2.89%; S = 2.34%; T = 3.23% and based on fuzzy logic controllers are: R = 0.15%; S = 0.11%; T = 0.13%.